Regenerative Supervision: A Restorative Approach for Counsellors Impacted by Vicarious Trauma - Neswald-Potter, Rhonda; Trippany Simmons, Robyn (Canadian Journal of Counselling and Psychotherapy, 2016)
Counsellors providing services for clients with traumatic material are vulnerable to vicariously experiencing emotional aspects of their clients’ experiences (Jordan, 2010). This vicarious experiencing, a phenomenon known as vicarious trauma (VT), can impact the counsellor’s functioning. The Regenerative Model is an expressive arts model of counselling supervision well-suited for processing the effects of VT. This article provides an overview of VT and its related phenomenon, vicarious posttraumatic growth (VPTG). An explanation follows of how the Regenerative Model may be employed to mitigate the effects of VT while facilitating development of VPTG. Case examples are included.